Holothuria (Selenkothuria) parva Krauss (in Lampert, 1885) (Holothuroidea: Holothuriida: Holothuriidae), new addition to the holothuroid fauna of Pakistan - Ahmed, Quratulan; Ali, Qadeer Mohammad; Shaikh, Iqra; Thandar, Ahmed (Zootaxa, 2025)
This paper provides the first record of Holothuria (Selenkothuria) parva Krauss (in Lamper, 1885) from the intertidal zone in Balochistan, Pakistan, on the northern shores of the Arabian Sea. We present a comprehensive description of this known species, illustrating its gross morphological characters and recording its habitat and expanding its known distribution now covering the western coastline of Pakistan its known distribution now covering also the western coastline of Pakistan. Identified specimens are deposited in the Marine Reference Collection and Resource Centre, University of Karachi (Cat. no. MRC&RC-UOK-Holo 27).